2019
DOI: 10.1158/1078-0432.ccr-18-2990
|View full text |Cite
|
Sign up to set email alerts
|

FDA Approval Summary: (Daunorubicin and Cytarabine) Liposome for Injection for the Treatment of Adults with High-Risk Acute Myeloid Leukemia

Abstract: On August 3, 2017, the FDA granted regular approval to Vyxeos (also known as CPX-351; Jazz Pharmaceuticals), a liposomal formulation of daunorubicin and cytarabine in a fixed combination, for the treatment of adults with newly diagnosed therapy-related acute myeloid leukemia (t-AML) or acute myeloid leukemia (AML) with myelodysplasiarelated changes (AML-MRC). Approval was based on data from Study CLTR0310-301, a randomized, multicenter, open-label, active-controlled trial comparing Vyxeos with a standard combi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
144
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 252 publications
(145 citation statements)
references
References 11 publications
0
144
0
1
Order By: Relevance
“…4 In the pivotal efficacy study (NCT01696084), VYXEOS provided a significant (p value = .005) improvement in overall survival of 9.6 months as compared to 5.9 months in the free drug control. 2,5 Importantly, this trial also showed that VYXEOS provided improved efficacy at a lower cumulative daunorubicin and cytarabine dose as compared to free drug counterparts. 6 Since 2016, the number of clinical trials of VYXEOS has increased from 7 to 21 with the most recent trials investigating the use of VYXEOS in additional patient populations (e.g., children; NCT03826992) and leukemias (e.g., lymphoblastic leukemias; NCT03575325).…”
Section: New Approvalsmentioning
confidence: 87%
See 3 more Smart Citations
“…4 In the pivotal efficacy study (NCT01696084), VYXEOS provided a significant (p value = .005) improvement in overall survival of 9.6 months as compared to 5.9 months in the free drug control. 2,5 Importantly, this trial also showed that VYXEOS provided improved efficacy at a lower cumulative daunorubicin and cytarabine dose as compared to free drug counterparts. 6 Since 2016, the number of clinical trials of VYXEOS has increased from 7 to 21 with the most recent trials investigating the use of VYXEOS in additional patient populations (e.g., children; NCT03826992) and leukemias (e.g., lymphoblastic leukemias; NCT03575325).…”
Section: New Approvalsmentioning
confidence: 87%
“…Since our previous article, three nanomedicines have been approved: Patisiran/ONPATTRO, VYXEOS, and NBTXR3/Hensify. VYXEOS is a combination chemotherapy nanoparticle, developed and marketed by Jazz Pharmaceuticals that, encapsulates a synergistic molar ratio of cytarabine to daunorubicin of 5:1 and received FDA approval for the treatment of acute myeloid leukemia in August of 2017 . VYXEOS are 100 nm bilamellar liposomes where the lipid membrane consists of desaturated phosphatidylcholine:distearylphosphatidylglycerol:cholesterol (7:2:1M ratio) .…”
Section: New Approvalsmentioning
confidence: 99%
See 2 more Smart Citations
“…To address this issue, nanocarrier‐based systems for codelivery of multiple drugs have increasingly been empoldered to offer a spatio‐temporal unification of separate pharmacokinetics of different drug payloads, which are evidenced to be more effective in preclinical and clinical studies . For instance, Vyxeos, a liposomal preparation coloaded with cytarabine and daunorubicin (5:1 molar ratio), has been approved by the U.S. Food and Drug Administration for acute myeloid leukemia treatment . Vyxeos can maintain a constant 5:1 drug ratio in the plasma of patients for up to 24 h after intravenous administration, which shows significantly enhanced anticancer efficacy with prolonged survival period compared with the conventional cocktail of cytarabine and daunorubicin (7:3 molar ratio) …”
Section: Introductionmentioning
confidence: 99%